2013
DOI: 10.1177/0309324712466550
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical model of the evolution of stress and strain fields in ultrafine-grained metal structures under tension

Abstract: In this study, the authors present a micromechanical finite element modelling approach to the analysis of a set of ultrafine-grained polycrystalline copper structures. The models take into account both realistic grain distribution and the number of refinement passes of the microstructure. The grain size effect is successfully predicted, with non-uniform deformation and shear localization reproduced during global plastic flow in agreement with experimental observations. The models provide a useful tool with whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The critical distance for a dipole dislocation to form is assigned a value of 7b. The volume fraction at the lath boundaries is defined as [56]:…”
Section: Parameter Identificationmentioning
confidence: 99%
“…The critical distance for a dipole dislocation to form is assigned a value of 7b. The volume fraction at the lath boundaries is defined as [56]:…”
Section: Parameter Identificationmentioning
confidence: 99%
“…Some groups of researchers used the quasireal (e.g., Voronoi tessellation based) representations of structures, with some real structure parameters, to represent realistic microstructures of nanometals [28][29][30][31] (see an example Figure 1c). So, Mercier et al [32] considered nanocrystalline material as an aggregate of spherical grains, with random grain sizes, distributed according to lognormal probability distribution.…”
Section: Multi-element Composite Models and Homogenizationmentioning
confidence: 99%
“…Using the Voronoi type composite model, Collini and Bonardi [30] demonstrated that the strength of nanometals depend on the strain variability, which in turn is controlled by the variation of grain sizes. According to [30], contributions of grains of different sizes to deformation are different.…”
Section: Multi-element Composite Models and Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain field zone has also been used to measure shear deformation of the materials. 18,19 However, all these studies have been limited to the surface view due to limited access to the internal deformation zone.…”
Section: Introductionmentioning
confidence: 99%